The Indicators of Reproductive Behavior in Young Families as a Criterion of the Social and Economic Level of the Society in Kazakhstan - GS Dauletova; LL Karp; KS Absattarova (Tehran University of Medical Sciences, 2012)
Background: In Kazakhstan, as in many other countries, a transformation of the traditional stereotypes of reproductive behavior, and change the types of family relationships is occurred. It is caused by social status changes, by the transformation of women's valuable orientations and social-role attitudes. The objective of this study was to identify the indicators of reproductive units and the motives for having children in the family. Methods: Designed questionnaires were used to study the regulation of fertility in young families, and women's views about the ideal, desired, and expected number of children per family. The survey covered 1017 respondents aged less than 39 years. Results: Expected number of children in the family depends on living conditions. The average expected number of children per family increases with improvement of living conditions and with increases in income. Statistically significant differences in the average expected number of children in families with a satisfactory and good income compared to poor income (P <0.001). Revealed the predominance of the expected, desired and ideal number of children among women of Asian ethnic group and on the desired and ideal number of children the differences were statistically significant (P <0.05). By mathematical formula that based on a poll can be calculated probability of birth of each child in the family. Conclusion: Reproductive attitudes of Astana women depend on age, educational level, income, professional employment, marital status, and ethnicity. The findings confirm the hypothesis that family plans are largely exposed to specific conditions of life.